2018
DOI: 10.1126/science.aar3958
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator condensation at super-enhancers links phase separation and gene control

Abstract: Super-enhancers (SEs) are clusters of enhancers that cooperatively assemble a high density of transcriptional apparatus to drive robust expression of genes with prominent roles in cell identity. Here, we demonstrate that the SE-enriched transcriptional coactivators BRD4 and MED1 form nuclear puncta at SEs that exhibit properties of liquid-like condensates and are disrupted by chemicals that perturb condensates. The intrinsically disordered regions (IDRs) of BRD4 and MED1 can form phase-separated droplets and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

111
1,868
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 1,910 publications
(2,136 citation statements)
references
References 83 publications
111
1,868
5
1
Order By: Relevance
“…Fluorescent microscopy of the droplet mixture revealed that OCT4 alone did not form droplets throughout the range of concentrations tested (Figure 3B). In contrast, purified recombinant MED1-IDR-GFP fusion protein exhibited concentration-dependent liquid-liquid phase separation (Figure 3B), as described previously (Sabari et al, 2018). …”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Fluorescent microscopy of the droplet mixture revealed that OCT4 alone did not form droplets throughout the range of concentrations tested (Figure 3B). In contrast, purified recombinant MED1-IDR-GFP fusion protein exhibited concentration-dependent liquid-liquid phase separation (Figure 3B), as described previously (Sabari et al, 2018). …”
Section: Resultssupporting
confidence: 86%
“…This enrichment was not seen using a randomly selected nuclear position (Figure S1). These results confirm that OCT4 occurs in puncta at the same SEs where Mediator forms condensates (Sabari et al, 2018) and where ChIP-seq shows co-occupancy of OCT4 and MED1 (Figure 1). …”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations